A new species of Klabonosa Bouček (Hymenoptera: Pteromalidae) reared from eggs of Endochus sp. (Hemiptera: Reduviidae) from India - Gupta, Ankita; Yeshwanth, H. M.; Sureshan, P. M. (Zootaxa, 2018)
The genus Klabonosa Bouček (Hymenoptera: Pteromalidae) is recorded for the first time from the Oriental region, with both sexes of K. indica Gupta, Sureshan & Yeshwanth sp. n. reared from eggs of the assassin bug Endochus sp. (Hemiptera: Reduviidae) on Artocarpus heterophyllus Lam. (Moraceae). The male is formally described and illustrated for the first time for the genus.